2018
DOI: 10.3390/ijms19082359
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding Transcriptome Maps across Twenty Tissues of the Korean Black Chicken, Yeonsan Ogye

Abstract: Yeonsan Ogye is a rare Korean domestic chicken breed whose entire body, including feathers and skin, has a unique black coloring. Although some protein-coding genes related to this unique feature have been examined, non-coding elements have not been widely investigated. Thus, we evaluated coding and non-coding transcriptome expression and identified long non-coding RNAs functionally linked to protein-coding genes in Ogye. High-throughput RNA sequencing and DNA methylation sequencing were performed to profile t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
0
5
1
Order By: Relevance
“…The expression of lncRNA has been breed-and tissue-specific. In our study, no lnc-TMEM184C found by Hong et al [62].…”
Section: Discussioncontrasting
confidence: 66%
“…The expression of lncRNA has been breed-and tissue-specific. In our study, no lnc-TMEM184C found by Hong et al [62].…”
Section: Discussioncontrasting
confidence: 66%
“…Using the RNA-seq technology, previous studies have identified 4404, 2481, 39,907, 8691, 1376, 6543, 2597 and 2056 lncRNAs in breast muscle, spleen, cerebrum, ovarian follicle, trachea, liver, testis and adipose of chickens, respectively [33,[92][93][94][95][96][97][98]. Moreover, Kern et al [99] found 9393 lncRNAs in eight tissue types (adipose, cerebellum, cortex, hypothalamus, liver, lung, skeletal muscle and spleen) of chickens and Hong et al [100] obtained 6900 lncRNAs genes in 20 different tissues (breast, gizzard, liver, pancreas, uterus, heart, bone marrow, kidney, cerebrum, cerebellum, eye, immature egg, mature egg, gall-bladder, comb, shank, skin, lung, spleen and fascia) of an individual Ogye, with c.75% of lncRNAs as tissue-specific. In the present study, 818 candidate lncRNAs were identified in the mid-segments of chicken small intestines.…”
Section: Discussionmentioning
confidence: 98%
“…By comparing the chicken genes to those of human, investigators found sequence and functional similarities of genes involved in cellular functions such as the immune response, environment adaptation, and reproduction (Dodgson and Romanov 2004a). Scientists have also investigated the non-coding transcriptome of the Gallus gallus genome and reported 9681 long non-coding RNAs according to the non-coding RNA (ncRNA) database NONCODE (Hong et al 2018). Previously considered as junk RNA, ncRNAs are now studied for their possible roles in regulation and conservation among vertebrates.…”
Section: Non-coding Rnamentioning
confidence: 99%